Determination of the optimum pre-drying treatment for making flour from Galiang (Cytosperma mekusii) from Daet, Camarines norte - Adlawan, Cresencio Bonifacio
Galiang being a minor root crop, has been ignored despite its potential as a source of food and a possible raw material in the food industry. This study aimed to determine the optimum pre-drying treatment for making flour from galiang tubers to obtain a good quality product at par - in quality and in price- with the highly used kinds of flour in the food industry. Market survey revealed that galiang flour satisfies some material specifications for a cereal and root crop flour substitute such as being a base and a thickener in snack foods and in soups/sauces, respectively, and as having good water absorption capacity. Specifications for galiang tubers for use in flour processing were established: maturity, three years; diameter, 25.4-55.88 cm; length, 12.7-25.4 cm; and dry matter content, 8-20%. Three batched of galiang flour were produced, each with a different pre-drying treatment, namely: steam blanching, sulfuring and control (no treatment). The major steps in production of flour are paring, slicing, pre-drying treatment, drying, and milling. After milling, the flour produced from each batch was assessed based on particle size, color, yield and cost. Results revealed that the sulfur-treated batch has the highest yield, and smallest particle size, has retained a yellowish color of galiang flesh, and has the lowest cost per unit mass. SO2 retention test showed that the sulfur-treated batch is 407.7 ppm below the maximum level of 500 ppm 32 days after milling.